Diseases Associated with Immune System Disorders in Allergic Diseases - Laylo, Davurova; qizi, Urinova Lola Abduvasi (American Journal of Bioscience and Clinical Integrity, 2025)
Some proteins and many polypeptide drugs (e.g., insulin, therapeutic antibodies) can directly stimulate antibody production. However, many drugs act as haptens, covalently binding to serum or cellular proteins, including proteins that make up the major histocompatibility complex (MHC) molecules. This binding makes the protein-drug complex immunogenic, stimulating antibody production and/or a T-cell response to the drug. Haptens can directly bind to MHC class II molecules and directly activate T lymphocytes. Some drugs act as prohaptens. Prohaptens are converted to haptens through metabolic reactions; For example, penicillin itself is not an antigen, but its major degradation product, benzylpenicilloic acid, can combine with tissue proteins to form benzylpenicilloyl (BPO), a major antigenic determinant. Some drugs bind directly to and stimulate T cell receptors (TCRs); the clinical significance of nonhapten binding to the TCR remains to be determined (1).